FILMS: CLIMBING INTO CULTURES BACKYARD - Stuart A Bruce (Celt: A Journal of Culture, English Language Teaching & Literature, 2005)
Learners of a second language must also learn about the culture of that language, not just as a way of supporting their linguistic competence, but as a way of understanding the role of the language in individuals and in society. Cultural Studies courses are a way of providing support for this need, and Moran (1992) suggests a useful framework for the learning/teaching of culture. Film is commonly used as a medium in teaching, and is an excellent resource for intercultural teaching because it is seen as being more than just a text. A case study at Soegijapranata Catholic University showed that films were preferred to other teaching methods, and were considered the best medium with which to teach culture, provided that discussion time was also provided. Student responses were overwhelmingly positive. The course was enjoyable, the film selections were regarded as useful sources of culture, and the course format and syllabus were considered effective. However, offence could be caused by sexual or violent content of films and suggestions are given to overcome this problem. Ways to support this teaching method include the introducing of cultural themes and backgrounds to students before films are presented, and the careful selection of films that are limited to one intercultural theme. Cultural Studies should be taught without any teacher-oriented preconceptions. Also, the medium of films should be included in a syllabus to improve the teaching/learning process and not for any other reason that could be seen as a misuse of this medium.